The health risk-benefit feasibility of nuclear power development. (1st July 2019) - Dai, Jing; Li, Shu; Bi, Jun; Ma, Zongwei
Abstract: Although nuclear power has gradually played an important role in world's energy consumption, there is still controversy because of the threat of releasing harmful radioactive substances. The public's incomplete understanding of nuclear power's risks and benefits has led to the Not In My Back Yard (NIMBY) effects all over the world, especially in developing countries. It is important to analyze the role that nuclear energy plays for human society in a multidimensional manner. Previous studies have investigated the benefits and risks of nuclear power, which mainly focus on economic benefits, and carbon or pollution emissions reduction benefits. Quantitative study on the comparison of health risks and benefits has been lacking. By taking China as an example, we compared the health risks and benefits of nuclear power using a health impact assessment methodology framework. The results show that, under normal operating conditions, the maximum annual disability adjusted life years (DALYs) caused by a single nuclear power plant would be 2.2 h and 11.4 h in 2020 and 2030, respectively. In 2030, the DALYs of the population exposed for 8 h within approximately 80 km of a plant would be between 108 and 9199 years in a severe accident scenario. The health benefits of nuclear power were calculated by avoided DALYs of reduced SO2, NOX, and PM10 of coal-fired power substituted by nuclear power. The avoided DALYs would be 501.0–1658.1 years and 676.4–2942.4 years in 2020 and 2030, respectively. Considering that risk equals consequence multiplied by the probability, developing nuclear power is risk-benefit feasible. More precise risk prevention, control measures and emergency plans (for both normal operation and accident conditions) of nuclear power plant should be put into place, and risk communication should be strengthened (e.g., bringing the scientific-based risk-benefit assessment results to the public, etc.) to reduce the public's NIMBY effects. Graphical abstract: Image 1 Highlights: By taking China as an example, health risk-benefit feasibility of nuclear power was assessed. Health benefits of nuclear power are much greater than risks in normal condition. Health lost are greater than benefits at IAEA level 5 or above nuclear accident. Development of nuclear power is health risk-benefit feasible. Precise risk control and communication for nuclear power are needed to avoid NIMBY.